Anatomical variations of the medial calcaneal nerve: a cadaveric study - Daniil G. Agafonov; Georgy A. Airapetov; Mikhail S. Serdobintsev; Nikolay I. Karpovich; Ruslan A. Khanmuradov; Denis G. Naumov; Mikhail A. Djeriev (Гений oртопедии, 2025)
Introduction One of the underestimated causes of pain in the heel area is neuropathy of the medial calcaneal nerve, which can both imitate and accompany plantar fasciitis. Some researchers note that neuropathy of the medial calcaneal branch of the tibial nerve is the cause of pain syndrome localized in the heel area. Knowledge of the main landmarks and anatomical variability of the medial calcaneal nerve passage in the foot can facilitate anesthesia, surgical interventions, including hydrodissection. Purpose To determine the anatomical variability of the medial calcaneal nerve, including the level of its origin, transverse diameter and topographic location relative to the main anatomical landmarks of the medial calcaneal area in order to use the obtained data in foot surgery, regional anesthesia and differential diagnosis of pain syndrome localized in the calcaneal area. Materials and methods Dissection of the medial heel region was performed in 16 cadavers (32 feet). For each specimen, we measured the thickness of the tibial and medial calcaneal nerves, as well as the distance (centimeters) from the tip of the medial malleolus to the point where the medial calcaneal nerve branched off from the tibial nerve, and to the bifurcation point of the tibial nerve into the medial and lateral plantar nerves. Results The study found that the medial calcaneal nerve branched from the tibial nerve at a distance of 2.7 ± 0.7 cm distal to the tip of the medial malleolus. The cross-sectional diameter of the nerve varied and averaged 1.9 ± 1.2 cm. In 15.6 % of cases, the medial calcaneal nerve had an additional branch. In the vast majority of cases (72 %), it terminated within the subcutaneous fat of the medial aspect of the calcaneous. Discussion The findings confirmed considerable anatomical variability of the medial calcaneal nerve. In 15.6 % of cases, it originated from the lateral plantar branch, which is consistent with the findings of other researchers. The morphological features of branching in the tibial nerve and its distal segments are of particular importance in foot surgery. Unintentional nerve injury is possible during interventions in the region of the tarsal tunnel (including radiofrequency denervation or endoscopic release). Conclusion This cadaveric study confirmed marked anatomical variability of the medial calcaneal nerve. These findings expand our understanding of the variable anatomy of the heel area and may aid in interpreting clinical cases of pain caused by compression or trauma to the medial calcaneal nerve, as well as in performing regional anesthesia.